Application of biodegradable plastic mulch improves manure N availability and tomato yield in an organic cropping system. (13th November 2020) - Han, Yingzuo; Sun, Wentao; Si, Pengfei; Lou, Chunrong; Wang, Jingkuan
Abstract: Low crop yield in organic farming restricts its popularization, and N deficiency is one of important reasons for the yield decline in organic farming. In this study, the biodegradable plastic mulch (BDP) was introduced into organic farming and its effects on soil N mineralization and crop yield were investigated. Over the two experimental years, application of manure + BDP improved the average soil moisture by 1.3% and 1.1%, and average soil temperature by 1.8 °C and 0.8 °C, and led to 27% and 26% higher cumulative mineralized N. Additionally, tomato fruit yield was improved by 18% and 18%, NUE increased by 104% and 77%, and N recovery rate greater by 60% and 48% in 2 years, respectively. Improvement of cumulative mineralized N was significantly correlated with soil temperature, while has no significant relationship with soil moisture. However, the tomato yield was obviously correlated with soil moisture, soil temperature, and N mineralization. This study suggested that the application of Manure + BDP improves the tomato yield due to its improvement on soil temperature, soil moisture, and accumulated mineralized N in organic tomato farming and implies that Manure + BDP can be considered as an option to improve the tomato yield in organic farming systems.